2010
DOI: 10.1088/0953-8984/22/7/075901
|View full text |Cite
|
Sign up to set email alerts
|

Phases in the (1 −x)Na0.5Bi0.5TiO3–(x)CaTiO3system

Abstract: The structures of (1 - x)Na(0.5)Bi(0.5)TiO(3)-(x)CaTiO(3) at room temperature have been investigated using neutron powder diffraction and dielectric studies. The system exhibits an orthorhombic (Pbnm) structure for x ≥ 0.15 and rhombohedral (R3c) for x ≤ 0.05. For x = 0.10, though the neutron diffraction pattern shows features of the orthorhombic (Pbnm) structure, Rietveld refinement using this structure shows a drastic reduction in the in-phase tilt angle (∼4°) as compared to the corresponding value (∼8°) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Only under tensile conditions the R3c structure can be stabilized. The results are in very good agreement with the experimental findings by Ranjan et al [37], who found for 0.05 < x < 0.15 coexistence of R3c and P bnm phases.…”
Section: A Alkaline Earth Metal Substituted Solid Solutionssupporting
confidence: 92%
See 1 more Smart Citation
“…Only under tensile conditions the R3c structure can be stabilized. The results are in very good agreement with the experimental findings by Ranjan et al [37], who found for 0.05 < x < 0.15 coexistence of R3c and P bnm phases.…”
Section: A Alkaline Earth Metal Substituted Solid Solutionssupporting
confidence: 92%
“…The crystal structures within the solid solution system (NBT) (1−x) -(CaTiO 3 ) x were investigated by Ranjan et al The authors reported on phase coexistence for 0.05 < x < 0.15 of rhombohedral R3c and orthorhombic P bnm structures [36,37], the latter is identical with the crystal structure of pure CaTiO 3 [38] and the high-pressure phase of pure NBT [27]. Watanabe et al analyzed the electrical properties and the phase transition temperatures of these materials for x 0.08 [39].…”
Section: Introductionmentioning
confidence: 99%
“…A coexistence of the ferroelectric (rhombohedral or tetragonal) and orthogonal phases has been reported in the A‐site disordered solid solution systems of BNT‐CT and BT‐CT . In the case of the BKT‐CT system, our study suggests that a pesudocubic phase is stable when the CT content reaches a certain amount.…”
Section: Resultssupporting
confidence: 59%
“…The majority of works mainly focused on the structural phase transition under different experimental conditions. Ranjan et al [48] showed by neutron diffraction and calculation of phase tilt angle that the (1-x)NBT-xCT system exhibits an orthorhombic phase (Pbnm) for x ≥ 0.15 and rhombohedral phase (R3c) for x ≤ 0.05 with a mixture of two phases (R3c+Pbnm) for x = 0.10. Moreover, Du et al [49] demonstrated that this system is susceptible to orthorhombic distortion for x ≥ 0.14 and the MPB was found to lie around 0.08 ≤ x < 0.14.…”
mentioning
confidence: 99%